Imagination First : Unlocking the Power of Possibility. - Liu, Eric (John Wiley & Sons, 2009)
When imagination becomes a habit, it can transform your work and your life. The best corporations know that innovative thinking is the only competitive advantage that cannot be outsourced. The best schools are those that create cultures of imagination. No wonder then that the decisions that compromise our economy, and even our national security, are often blamed on the "failure of imagination." This book introduces us to a wide variety of individuals who have learned how to make a habit of imaginative thinking and creative action. It offers a set of universal practices that anyone ca.